Brain damage after cardiopulmonary by-pass: correlations between neurophysiological and neuropathological findings. Issue 10 (October 1981) - Malone, M; Prior, P; Scholtz, C L
Abstract : Ischaemic lesions along cerebral arterial boundary zones were present in nine patients dying after cardiopulmonary by-pass. Their intra-operative cerebral function monitor recordings had shown at least 7 min major depression, its severity correlating with degrees of neurological deficit after operation and EEG abnormality and extent of infarction. In contrast eleven patients with normal or minimally abnormal cerebral function monitor recordings had macroscopically normal brains.